Agreement between Arterial and Venous Blood Gases In Emergency Medical Care: A Systematic Review. Issue 3 (May 2013) - Kelly, AM
Aim: The objectives of this review are to describe the agreement between arterial and venous blood gas values for pH, pCO2, bicarbonate and base excess. Methods: MEDLINE search of papers published 1966-September 2012 for studies comparing arterial and peripheral venous blood gas values for any of pH, pCO2, bicarbonate and base excess in adult patients with any condition in an emergency department setting. The outcome of interest was mean difference weighted for study sample size. Results: The weighted mean arterio-venous difference in pH was 0.034 pH units (n=2087), with narrow limits of agreement. The weighted mean arterio-venous difference for pCO2 was 6.2 mmHg (n=1043), but with 95% limits of agreement up to the order of ±20mmHg. Venous pCO2 <45 mmHg has 100% sensitivity and negative predictive value for prediction of arterial hypercarbia (n=529). For bicarbonate, the weighted mean difference between arterial and venous values was −1.20 mEq/L (n=1403), with 95% limits of agreement of the order of ±5 mmol/L. Regarding base excess, the mean arterio-venous difference was 0.4 (n=295) but data are conflicting regarding the width of 95% limits of agreement. Conclusion: For patients who are not in shock, venous pH and bicarbonate have sufficient agreement to be clinically interchangeable for arterial values. Agreement between arterial and venous pCO2 is too poor and unpredictable to be clinically useful as a one-off test but venous pCO2 may be useful to screen for arterial hypercarbia.